2018
DOI: 10.1051/matecconf/201815301007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on porous media combustion characteristics using different discrete materials

Abstract: Occurrence of combustion phenomenon in porous media has always excited researchers to develop various shape and size of burner so that maximum utilization of energy can be taken achieved. Here in this experiential work, dual layer micro burner was exclusively built to carry out porous media combustion characteristic with different type of discrete material in reaction zone. Presently, only alumina and zirconia are compared in discrete form, while preheat layer was made of porcelain ceramic material (foam type)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Sahu et al [8] studied Glass/Carbon/Kevlar reinforced polymer composite to obtain natural frequency numerically. Also effect of hybridization on natural frequency of composites [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Sahu et al [8] studied Glass/Carbon/Kevlar reinforced polymer composite to obtain natural frequency numerically. Also effect of hybridization on natural frequency of composites [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the flame stability limit decreased in the order of ceramic foam (10 PPI), packed bed (13 mm) and honeycomb ceramic (200 CPSI) at the equivalence ratio of 0.6. Similarly, by adopting the different discrete materials, it was found that the thermal efficiency of zirconia pellets was the highest at the equivalence ratio of 0.6 24 . Shi et al 25 numerically studied the two‐dimensional packed bed with staggered connected pellets.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, by adopting the different discrete materials, it was found that the thermal efficiency of zirconia pellets was the highest at the equivalence ratio of 0.6. 24 Shi et al 25 numerically studied the two-dimensional packed bed with staggered connected pellets. When the porosity was set to 0.4, the normalized velocity of the mixed gas in the reaction zone was 18.5 times than that in a uniformly arranged burner.…”
Section: Introductionmentioning
confidence: 99%